The geology and palladium mineralization of the southern Roby, Twilight, and High Grade zones of the Lac des Iles Mine, western Superior province of Canada - Hinchey, John Glenn (University of Ottawa (Canada), 2005)
The Lac des Iles Pd mine is hosted by 2.69 Ga. gabbroic rocks of the Lac des Iles Intrusive Complex in the southern Wabigoon subprovince, Superior province of Canada. Economic mineralization, ∼ 159 Mt at 1.55 g/t Pd before major mining in 2001, occurs in the Roby zone of the Mine Block Intrusion. The southern Roby and Twilight zones contain gabbroic/gabbronoritic intrusions with complicated textures, such as brecciation and magma mingling. Ore has low concentrations of sulphide (∼ 1-3 vol. %) and high Pd/Pt of ∼8-10. Detailed mapping and geochemical analysis of the southern Roby and Twilight Zones indicate that early leucocratic rocks are barren and that the bulk of the platinum group elements (PGE) were introduced by late melanocratic magmas. Sulphur correlates positively with base and precious metals. In addition to exsolution of pentlandite and chalcopyrite from pyrrhotite, the data suggests a magmatic origin of the PGE where immiscible sulphide melt concentrated PGE. Fractionation of olivine, chromite, and high temperature platinum group minerals likely resulted in high concentrations of Pt-group PGE/Ir-group PGE in the parental magmas. Extreme enrichment of Pd and high Pd/Pt ratios in the late melanocratic magmas is interpreted to be due to incorporation of earlier formed sulphide melt. The High Grade Zone, on the eastern margin of the Roby Zone, contains only ∼7 vol. % of the Roby Zone but hosts ∼ 35% of the Pd at the mine. The zone is intensely altered and contains two mineral assemblages: (a) millerite + siegenite +/- chalcopyrite +/- pyrite co-existing with hornblende + plagioclase +/- quartz +/- carbonate, and (b) pyrite +/- chalcopyrite with chlorite + actinolite +/- albite +/-quartz +/- carbonate. The ore is high in Pd and Pd/Pt (mean of 16.5; max. 25) compared to the southern Roby and Twilight zones. Although plots of S versus Se and base and precious metals show scatters, positive correlations are observed for Se versus Te and less mobile elements, such as Pt, Ni and Co. The data suggest that magmatic mineralization was followed by hydrothermal transport of mobile elements. Hydrothermal activity enriched the zone by up to 40 ppm Pd. The lack of fluid pathways and the distribution of the zone adjacent to mineralized breccia are consistent with magmatic-hydrothermal activity by aqueous fluids exsolved from the parental magmas of the Roby zone. Geochemical and Pb, Sr, and Nd isotope compositions from the Mine Block Intrusion suggest that the parental magmas were derived through high degrees of partial melting of a previously metasomatized depleted mantle source. The Lac des Iles Intrusion, as well as the surrounding mafic/ultramafic and sanukitoid suite of intrusions, display subduction influenced geochemical signatures, such as negative HFSE and enriched LILE. (Abstract shortened by UMI.)
Keywords: Geology.; Geochemistry.